EUREKA CONVERTER: A MODIFIED BUCK CONVERTER - Muhammad Kashif Khan; Kifayat Ullah; Bilal Ur Rehman; Muhammad Amir; Muhammad Farooq; Salman Ilahi Siddiqui, Wasim Habib (Spectrum of Engineering Sciences, 2025)
This paper presents a modified form of DC-DC Buck converter and elaborates its operation in continuous conduction mode. The proposed model is based on the original Buck converter topology with extra modifications. In relation, the elementary voltage transfer function and the accompanying proposed circuit equations are also worked out in this paper. Ripple factor and difference between actual and target voltage has been reduced. Performance analysis of the proposed design is also carried out in considerable depth.